COMPLEMENTARY THERAPIES IN ASTHMATIC CHILDREN - PROF. N.VIJAYALAKSHMI; DR. P.PARAMANANDAM (International Journal of Pharma and Bio Sciences, 2015)
Better health is central to human happiness and well-being. It also makes an important contribution to economic progress, as healthy populations live longer, are more productive, and save more. Children need to be healthy to reach their full potential. Managing children with asthma is a real challenge in the new millennium. Clinical trials have shown that risks are reduced with effective complementary therapies and with regular medications. Therefore the present scenario demands for specific intervention to improve the pulmonary function among children with asthma. A wide range of treatments exists under the umbrella term of ‘complementary therapy’. Each treatment has its own unique theory and practice, which makes it difficult to offer a blanket definition. Diseases and illness are viewed as mechanical break downs and generally these break downs and the symptoms that caused are treated. Complementary therapies aim to treat the entire person, not just the symptoms. Some of the complementary therapies are Acupuncture, Alexander technique, Aroma therapy, Bio feedback, Buteyko Technique, Chiropractic Technique, Homeopathy, Hydrotherapy, Massage, Naturopathy, Reiki, Salt Therapy, Yoga. These Complementary Therapies increases the efficiency of each breath, improves lung capacity, increases flow of oxygen to all parts of the body, improve abdomen and diaphragm control , increases relaxation and calmness by releasing tension. Complementary and alternative medicine (CAM) is being increasingly used by consumers along with conventional medical care. The widespread use of CAM therapies has implications not only for research but also for the education of conventional health care professionals. Health care professionals need to be informed about CAM and knowledgeable enough to discuss with their patients about CAM therapies. Furthermore, advances in understanding and applying CAM that derive from basic or clinical research should be incorporated into the pre-professional and continuing education programs of all relevant health professionals.